Using citizen science to describe the prevalence and distribution of tick bite and exposure to tick-borne diseases in the United States - Nieto, Nathan C.; Porter, W. Tanner; Wachara, Julie C.; Lowrey, Thomas J.; Martin, Luke; Motyka, Peter J.; Salkeld, Daniel J. (PLOS ONE, 2018)
Tick-borne pathogens are increasing their range and incidence in North America as a consequence of numerous factors including improvements in diagnostics and diagnosis, range expansion of primary vectors, changes in human behavior, and an increasing understanding of the diversity of species of pathogens that cause human disease. Public health agencies have access to human incidence data on notifiable diseases e.g., Borrelia burgdorferi, the causative agent of Lyme disease, and often local pathogen prevalence in vector populations. However, data on exposure to vectors and pathogens can be difficult to determine e.g., if disease does not occur. We report on an investigation of exposure to ticks and tick-borne bacteria, conducted at a national scale, using citizen science participation. 16,080 ticks were submitted between January 2016 and August 2017, and screened for B. burgdorferi, B. miyamotoi, Anaplasma phagocytophilum, and Babesia microti. These data corroborate entomologic investigations of tick distributions in North America, but also identify patterns of local disease risk and tick contact with humans throughout the year in numerous species of ticks and associated pathogens.